2017
DOI: 10.17116/terarkh2017891123-127
|View full text |Cite
|
Sign up to set email alerts
|

Chronic obstructive pulmonary disease concurrent with metabolic syndrome: Pathophysiological and clinical features

Abstract: Chronic obstructive pulmonary disease (COPD) still remains a serious public health problem, which is a common cause of disability and death in the able-bodied population. Furthermore, the number of patients with metabolic syndrome (MS) is steadily increasing worldwide. Recently, there is also an increase in the number of patients with COPD concurrent with MS, which is a mutually confounding risk factor for concomitant cardiovascular disease and adversely affects prognosis in these patients. Systemic subclinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 33 publications
0
4
0
2
Order By: Relevance
“…The analysis of the literature suggests that hypothyroidism in manifest or subclinical forms is quite common among the comorbidities that can affect the prognosis of HF [33][34][35]. The differences in these groups of patients in terms of overall mortality can be explained by the heterogeneity of the groups by sex, age, degree of TSH level change and duration of follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the literature suggests that hypothyroidism in manifest or subclinical forms is quite common among the comorbidities that can affect the prognosis of HF [33][34][35]. The differences in these groups of patients in terms of overall mortality can be explained by the heterogeneity of the groups by sex, age, degree of TSH level change and duration of follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoarthritis (OA) is one of the less studied comorbidities of asthma. It has been shown that prevalence of osteoarthritis in patients with asthma is significantly higher compared with chronic obstructive pulmonary disease and subjects with no respiratory diseases [9,10]. Mahmood Z. et al found that asthmatic patients who had higher rate of emergency hospitalizations also had a higher risk of developing OA [11].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of comorbidities is quite high: more than 50% of patients with COPD have 1–2 comorbidities, 15.8% have 3–4, and 6.8% have more than 5 [6]. In general, in patients with COPD, attention is paid to the following pathologies: cardiovascular diseases, osteoporosis, skeletal muscle dysfunction, weight loss [7,8,9]. However, it is important to take into account such conditions as anxiety and depression, which, according to several studies, significantly affect the course of the disease.…”
Section: Introductionmentioning
confidence: 99%